The Barriers of Teaching Speaking English for EFL Learners - Nuraini, Kristi (Universitas Muhammadiyah Jember, 2016)
This research portraits the barriers in teaching speaking for EFL learner. The barriers in teaching speaking English come form two aspects: internal and external factors. Internal factors are native language, age, exposure, innate phonetic ability, identity and language ego, and motivation concern for good speaking English and external factors are teaching speaking English at large class and learners’ autonomy. Each barrier is connected with the available method used in teaching speaking English. The conclusion of this research is teacher must focus on the learners need, the second is teacher applies for environment analysis before conducting teaching speaking English, the last is teacher chooses the suitable method based on the problems that he/she found in his/her teaching speaking English. Several methods that are often used in teaching speaking English are Direct Method, The Silent Way, Community Language Learning, Total Physical Response, and Communicative Language Teaching.Keywords: barriers in teaching speaking, internal factors, external factors